Adjusting the labor supply to mitigate violent shocks: evidence from rural Colombia (2011)
This paper studies the use of labor markets, changes in on and off-farm work, to mitigate the impact of violent shocks on households in rural areas in Colombia. Because the incidence of violent shocks is not exogenous, the analysis uses instrumental variables that capture the benefits of exercising presence. As a response to the violent shocks men decrease the time devoted to off-farm agricultural activities and increase the off-farm non-agricultural activities while women decrease their leisure time and increase the time devoted to household chores and childcare. These changes in time-use suggest large drops in agricultural production. In addition, because the decrease in off-farm agricultural activities is larger than the increase in non-agricultural activities, labor markets appear unable to fully absorb the additional labor supply. Policies in conflict-affected countries should go beyond short-term relief and aim at preventing labor markets from collapsing and at supporting the recovery of agricultural production.